The Sintesis dan Karakterisasi Komposit Fe3O4/Kitosan/Kaolin Bangka - Eva Julianti; Verry Andre Fabiani; Ristika Oktavia Asriza (Stannum : Jurnal Sains dan Terapan Kimia, 2020)
Synthesis and characterization of Fe3O4/chitosan/clay Bangka has been carried out. Synthesis of composite was done with variations the composition of clay (0; 25; 50; 100 %) at the composition of Fe3O4 95 mg of Fe3O4 and 1 gr of chitosan. Characterization of composite Fe3O4/chitosan/clay have been analysed with XRD, FTIR, porosity test, the degree of development, and adsorption efficiency test for Cu2+ ion. The results of the analysed with XRD show the difractogram of clay and Fe3O4 at 2θ= 8,92o, 29,57o, and 45,61o (clay); 26,90o, and 35,64o (Fe3O4). Results of the analysed with ftir show the spectrum of the chitosan, clay, and Fe3O4 at 3825, 3689, 2103, 1425 cm-1 (chitosan), 1028, 884,41 cm-1 (clay), 791,11 cm-1 (chitosan) and 696,95 cm-1 (Fe3O4). The results of porosity test and the degree of development showed the high point are 1,547 and 754,63% without composition of clay. The adsorption test for Cu2+ ion show percentage of adsorption efficiency is 72,41% at composite of Fe3O4/chitosan with the clay added 1 gr.